Project Scheduling By using Goals Programming – An Applied Research In Modern Village Project (Residential Building Aspectin In Wasit Governorate) - خلف وقاص سعد; خضر تمام سلمان (Journal of Economics and Administrative Sciences, 2015)
One of the most important challenges facing project management at present time is to ensure project accomplishment in spite of the specific restrictions like the specific time the financial resources specialized to do the project ; which require an accurate consideration for time and cost . the modern village project (residential building aspect) is one of the great project that ministry of agriculture is trying to do Wasit governorate it is chosen as the work in this project is dilatory for that is being studied in term of some modern mathematical and scientific methods like critical path method (CPM)which is one of the project management and scheduling methods to know the time needed to accomplish residential building project , with acknowledgement that many activities of project net are of unconventional relations among each others (of type finish to start) ; and there are periods of (lead and lag) among each other for that reason , (primavera V6) program is used in project scheduling and management which is one of prime programs to find the time and cost of project accomplishment at normal and crash states ; and as project management has numerous goals , same of them are contradictory which are trying to do in one time and that require great working and decision-makers face difficulty to reach into accurate and suitable decisions (goal programming) method is used which is one of efficient and mathematical method to achieve the objectives the results obtained of the mathematical model solution with the use of (win Q.S.B V2) program show the importance and efficiency of this method in modern village project scheduling (residential building aspect) under numerous contrasted goal that project management determined according to their importance and to be achieved according to their importance and to be achieved in one time